Thermal Performance of Film Cooling for Two Staggered Rows of Circular Jet - Assim H. Yousif; Amer M. Al-Dabagh; Muwafag Sh. Alwan (Engineering and Technology Journal, 2013)
The holes orientation and jet inclination angles are important parameters that control the development of the flow structures and the penetration and spreading of the jets. Experimental investigations that describe the film cooling performance for a two rows of staggered holes with opposite orientation angles are presented to determine the heat transfer coefficient and film effectiveness under different holes attitude. Experimentalin vestigations were done on a flat plate by using a single test transient IR thermograph technique. The attitude of the downstream row holes is fixed at inclination angle (θ=30°) and orientation angle of (Ɣ=0°), while the upstream row holes is fixed with opposite orientation angle (Ɣ=180°) and the inclination angles are changed three times as (θ=20°, 30°, and40°). Three different blowing ratios (BR) =0.5, 1.0, and 1.5 are used in experimental program at each case. Enhancements were observed, in which as theblowing ratio increased and the inclination angle of upstream row decreased, the film cooling effectiveness and heat transfer coefficient are increased.